Электрофизические характеристики комбинированного пленочного диэлектрика на основе полипропиленовой и полиэтилентерефталатной пленок - Гунько, Виктор Иванович; Дмитришин, Алексей Ярославович; Топоров, Сергей Олегович (НТУ "ХПИ", 2017)
Рассмотрены результаты исследований электрофизических характеристик различных конструкций комбинированного полипропиленово-полиэтилентерефталатного диэлектрика для высоковольтных импульсных конденсаторов. На основе проведенных экспериментов на макетах секций конденсатора проанализированы факторы, влияющие на электрическое сопротивление изоляции и кратковременную электрическую прочность таких диэлектрических структур.

Results of researches of the electrical characteristics of various designs combined polypropylene (PP) - polyethylene terephthalate (PET) dielectric for high-voltage pulse capacitors are reviewed. On the basis of experiments on mockups of the capacitor sections are analyzed factors, such as the polarity of the capacitor platesand films, affecting the electrical insulation resistance and short-term dielectric strength of such dielectric structures. Recommendations about using dielectric structures as capacitor insulation are given. It is found that with an increase of the polar component in the dielectric film structure electric insulation resistance decreases.
Electrophysical characteristics of the combined film dielectric based on polypropylene and polyethylene terephthalate films
Keywords: полярность диэлектрика; электрическое сопротивление изоляции; электрическая прочность; высоковольтный импульсный конденсатор; dielectric polarity; electrical insulation resistance; dielectric strength